Comparative Modelling of Organic Anion Transporting Polypeptides: Structural Insights and Comparison of Binding Modes - Tonduru, Arun Kumar; Adla, Santosh Kumar; Huttunen, Kristiina M; Kronenberger, Thales; Poso, Antti (Molecules (Basel, Switzerland), 2022)
To better understand the functionality of organic anion transporting polypeptides (OATPs) and to design new ligands, reliable structural data of each OATP is needed. In this work, we used a combination of homology model with molecular dynamics simulations to generate a comprehensive structural dataset, that encompasses a diverse set of OATPs but also their relevant conformations. Our OATP models share a conserved transmembrane helix folding harbouring a druggable binding pocket in the shape of an inner pore. Our simulations suggest that the conserved salt bridges at the extracellular region between residues on TM1 and TM7 might influence the entrance of substrates. Interactions between residues on TM1 and TM4 within OATP1 family shown their importance in transport of substrates. Additionally, in transmembrane (TM) 1/2, a known conserved element, interact with two identified motifs in the TM7 and TM11. Our simulations suggest that TM1/2-TM7 interaction influence the inner pocket accessibility, while TM1/2-TM11 salt bridges control the substrate binding stability.
Keywords: organic anion transporting polypeptides (OATPs); xenobiotic transporters; biologický transport; Organic Anion Transporters; Solute-Carrier O (SLCO); homology models; přenašeče organických aniontů; Biological Transport; molecular dynamics simulations